ASME 2011 5th International Conference on Energy Sustainability, Parts A, B, and C 2011
DOI: 10.1115/es2011-54720
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Effect of Reynolds Number on Airfoil Performance

Abstract: The standard of living throughout the world has increased dramatically over the last 30 years and is projected to continue to rise. This growth leads to an increased demand on conventional energy sources, such as fossil fuels. However, these are finite resources. Thus, there is an increasing demand for alternative energy sources, such as wind energy. Much of current wind turbine research focuses on large-scale (>1 MW), technologically-complex wind turbines installed in areas of high average wind speed (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The importance of appropriate aerofoil data for low Reynolds number applications has been well established in the analysis of small wind turbines (24,(30)(31)(32) , and the same holds true for small propellers (9,13,23) . When using blade element analysis methods, aerodynamic data is commonly obtained for a single Reynolds number, taken at 70-75% of the radius (17,33,34) ;…”
Section: Attached-flow Aerodynamic Analysismentioning
confidence: 97%
“…The importance of appropriate aerofoil data for low Reynolds number applications has been well established in the analysis of small wind turbines (24,(30)(31)(32) , and the same holds true for small propellers (9,13,23) . When using blade element analysis methods, aerodynamic data is commonly obtained for a single Reynolds number, taken at 70-75% of the radius (17,33,34) ;…”
Section: Attached-flow Aerodynamic Analysismentioning
confidence: 97%
“…It has been reported that increased lift coefficients in parallel with the increase in turbulence levels. Burdet et al [14] used PROFIL (Eppler Airfoil Design and Analysis Code) and XFOIL software to examine the effect of Reynolds number on the E387 wing profile. It is argued that the design angle of attack depends on the Reynolds number and that the PROFIL data lead to a difference of more than 3 degrees compared to the experimental data for wind turbine blade design.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the airfoil with 30% varying thickness demonstrated better aerodynamic characteristics compared to the baseline airfoil. Burdett et al [16] extensively validated the aerodynamic results of S823 and E387 airfoils invoked from PROFIL and XFOIL numerical codes with the experimental data. The research work shows that the design angle of attack estimated by numerical simulations were around 2.5% lesser than the experimental techniques.…”
Section: Introductionmentioning
confidence: 99%